Tunneling time probed by quantum shot noise - Pierre Février (Nature Portfolio, 2018)
The time that a particle takes to traverse an electronic junction by tunneling has been discussed in theory but not detected directly. Here, the authors take advantage of both optical and electronic information from a tunnelling event to estimate this traversal time at around 1.1 femtosecond.